Description of the tadpoles of Proceratophrys cristiceps (Anura: Cycloramphidae, Odontophrynini) - Da Silva Vieira, Washington Luiz; Da Silva Vieira, Kleber; Santana, Gindomar Gomes (Zootaxa, 2007)
The tadpoles of Proceratophrys cristiceps (Müller, 1884) are described based on specimens collected in a temporary pool at the Estação Experimental de São João do Cariri, in the municipality of São João do Cariri, Paraíba State, in NE Brazil. Tadpoles in stage 39 had a total length of 30.31 mm, a body length of 12.45 mm (corresponding to 41.07% of their total length), were ovoid shaped in dorsal view, slightly depressed in lateral view, and with a dental formula 2(2)/3(1). The morphological characteristics of the tadpole P. cristiceps were compared with other tadpoles of four species belonging to the Proceratophrys bigibbosa group.